2017
DOI: 10.3390/ijerph14020128
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine and Fine Particulate Matter Inside and Outside of Mechanically Ventilated Buildings

Abstract: The objectives of this study were to measure levels of particulate matter (PM) in mechanically ventilated buildings and to improve understanding of filtration requirements to reduce exposure. With the use of an Ultra High Sensitivity Aerosol Spectrometer and an Aerodyne Mass Spectrometer, ultrafine (0.055–0.1 μm) and fine (0.1–0.7 μm) indoor and outdoor PM was measured as a function of time in an office, a university building, and two elementary schools. Indoor particle levels were highly correlated with outdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[20] Accurate evaluation of the distribution of ultrafine particulate matter in air is of utmost significance to public health, especially for children. [21,22] However, the detection of FPs and UFPs posed major challenges as the commonly used PM 2.5 index fails to provide size distribution for FPs and UFPs. Benefitting from the advancement of nanotechnology, Yu et al, demonstrated a size spectrometer by using a nanofiber array for probing FPs and UFPs with an unprecedented size resolution of 10 nm ( Figure 7).…”
Section: Fine Particle and Ultrafine Particle Analysismentioning
confidence: 99%
“…[20] Accurate evaluation of the distribution of ultrafine particulate matter in air is of utmost significance to public health, especially for children. [21,22] However, the detection of FPs and UFPs posed major challenges as the commonly used PM 2.5 index fails to provide size distribution for FPs and UFPs. Benefitting from the advancement of nanotechnology, Yu et al, demonstrated a size spectrometer by using a nanofiber array for probing FPs and UFPs with an unprecedented size resolution of 10 nm ( Figure 7).…”
Section: Fine Particle and Ultrafine Particle Analysismentioning
confidence: 99%
“…This is probably due to higher particle generation in places where the volunteers carried out activities for this occupation category, most of the time in the center of the city, where there is an intense flow of vehicles. Additionally, fine particles are transported and accumulated inside workplaces, and thus increasing the level of exposure (Wu et al, 2012;Miller et al, 2017). The 'transport' presented the largest mass concentrations in larger sizes, probably associated with the resuspension material from auto-related activity.…”
Section: Personal and Environmental Particle Concentrationsmentioning
confidence: 99%
“…Airborne particles in buildings come from the outdoors through the building envelope with infiltrating air or the ventilation system's leakages. [7][8][9][10][11][12] Two existing strategies have been widely used to control IAQ in buildings: installing a high-efficiency air filter system 10,[13][14][15] and increasing the ventilation rate. 10,13,[16][17][18][19][20] In mechanically ventilated buildings, the outdoor particles, which infiltrate through gaps in the building's envelope with the infiltration air, could directly impact IAQ.…”
Section: Introductionmentioning
confidence: 99%